Validation of an In Vitro Mutagenicity Assay Based on Pulmonary Epithelial Cells from the Transgenic MutaMouse: Intra-Laboratory Variability and Metabolic Competence - Hanna, Joleen (Université d'Ottawa / University of Ottawa, 2018)
Genetic toxicity tests used for regulatory screening must be rigorously validated to ensure accuracy, reliability and relevance. Hence, prior to establishment of an internationally-accepted test guideline, a new assay must undergo multi-stage validation. An in vitro transgene mutagenicity assay based on an immortalized cell line derived from MutaMouse lung (i.e., FE1 cells) is currently undergoing formal validation. FE1 cells retain a lacZ transgene in a λgt10 shuttle vector that can be retrieved for scoring of chemically-induced mutations. This work contributes to validation of the in vitro transgene (lacZ) mutagenicity assay in MutaMouse FE1 cells. More specifically, the work includes an intra-laboratory variability study, and a follow-up study to assess the endogenous metabolic capacity of FE1 cells. The former is essential to determine assay reliability, the latter to define the range of chemicals that can be reliably screened without an exogenous metabolic activation mixture (i.e., rat liver S9). The intra-laboratory variability assessment revealed minimal variability; thus, assay reproducibility can be deemed acceptable. Assessment of metabolic capacity involved exposure of FE1 cells to 5 known mutagens, and subsequent assessment of changes in the expression of genes involved in xenobiotic metabolism; induced transgene mutant frequency (±S9) was assessed in parallel. The results revealed that the FE1 cell line is capable of mobilising several Phase I and Phase II gene products known to be involved in the bioactivation of mutagens. Collectively, the results presented support the contention that the FE1 cell mutagenicity assay can be deemed reliable and reproducible. Consequently, the assay is an excellent candidate for continued validation, and eventual establishment of an OECD (Organization for Economic Cooperation and Development) Test Guideline.
Keywords: Genotoxicity; Assay Validation